Well, that was awkward - Vail, Rachel (Puffin Books, 2018)
Eighth-grade student Gracie Grant has a huge crush on handsome, popular AJ Rojanasopondist. The only problem is, AJ likes her best friend, Sienna. Grace quickly overcomes the tinge of jealousy she feels upon learning the news, and happily helps Sienna craft responses to AJ's surprisingly funny text messages. Unbeknownst to the girls, there's a good reason the messages seem out of character for AJ--his buddy Emmett is writing them on his behalf.